RETRACTED: Language wealth of primary school students, its tasks - Qo’ldoshev Rustambek; Hamroyev Alijon; Jumayeva Habiba; Abulova Zilola; Xayrullayeva Dilnoza; Niyazova Moxichehra (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001